Continuous annealing of medium-Mn steels: Plasticity controlled by SIMT kinetics through grain size distribution and Mn concentration in retained austenite - Adam Skowronek (Materials & Design)
Intercritical annealing, a process widely employed to achieve a high fraction of retained austenite in medium-Mn steels, typically requires several hours, resulting in low economic efficiency. Alternatively, flash annealing, characterized by high heating rates, relies on induction heating, which introduces technological complexity and limits industrial applicability. Both methods are considered either economically inefficient or technically challenging to implement on a large scale. In this study, a novel continuous annealing method is proposed, designed to be compatible with existing industrial installations. This method enables the production of steel with a significantly improved UTS × TEl product. Compared to conventional intercritical annealing, the proposed method produces a lower Mn enrichment of austenite. However, the retained austenite exhibits significantly finer lath thickness, tuning its stability. This structural modification facilitates an intense and gradual martensitic transformation across the entire deformation range, contributing to improved strain hardening and plasticity. The analysis also reveals a strong correlation between the strain hardening behavior of the steel and the calculated stability of the retained austenite. These findings provide a detailed description of the kinetics of strain-induced martensitic transformation, offering valuable insights into the material’s plastic performance.